Pengaruh Sikap, Kepedulian Lingkungan, Dan Kesediaan Untuk Membayar Terhadap Niat Beli Skincare Ramah Lingkungan Dimoderasi Eco-literacy - Vita Apriana; Aniek Hindrayani; Jonet Ariyanto Nugroho (Journal on Education, 2023)
This research aims to (1) determine the influence of attitudes on the intention to purchase environmentally friendly skincare among teenagers in Surakarta, (2) determine the influence of concern on the intention to purchase environmentally friendly skincare among teenagers in Surakarta, (3) determine the influence of willingness to pay on the intention to purchase skincare environmentally friendly among teenagers in Surakarta, (4) to find out whether eco-literacy strengthens the influence of attitudes on the intention to buy environmentally friendly skincare among teenagers in Surakarta, (5) to find out whether eco-literacy strengthens the influence of environmental concern on the intention to buy environmentally friendly skincare in teenagers in Surakarta, (6) to find out whether eco-literacy strengthens the influence of willingness to pay on the intention to buy environmentally friendly skincare among teenagers in Surakarta. This research is a quantitative descriptive research with 97 female adolescent research subjects in Surakarta. The sampling technique uses a purposive sampling technique. Data collection uses a questionnaire distributed online via Google Forms. The validity test technique used is Pearson Product Moment. Data analysis uses multiple regression with Moderate Regression Analysis (MRA). The research results showed that the variables attitude (0.016 < 0,05), environmental concern (0.001 < 0,05), and willingness to pay (0.009 < 0,05) had a significant positive effect on the intention to purchase environmentally friendly skincare. Meanwhile, the interaction of attitude variables, environmental concern, and willingness to pay with eco-literacy failed to strengthen its influence on purchase intention.